Comparison of the Use of Plant Growth Regulators (PGR) of Red Onion and Shallot Extracts on the Growth of Green Spinach Plants (Amaranthus sp.) - Fransiska, Yuni; Anggarani, Mirwa Adiprahara (Jurnal Pijar Mipa, 2024)
Green spinach is one type of vegetable commodity that the people of Indonesia most widely consume because it has a relatively high nutritional content such as iron, vitamin C, protein, and carbohydrates. However, currently, there is a decrease in green spinach vegetable productivity in Indonesia due to several things, including cultivation techniques that could be more optimal, low seed quality, and limited application of agricultural technology. For this reason, agrarian intensification is needed by using natural plant growth regulators (PGR) to increase the growth of green spinach. Red onions and shallots are part of the allium genus, which has growth phytohormones, namely auxin and gibberellins, which have the potential to be natural PGR. This study aims to compare the use of red onion and shallot extracts in increasing the growth of green spinach plants. The research design used was a randomised group design (RGD) with variations in extract concentrations (0%, 15%, 30%, 45%). Parameters of observation of green spinach plant growth are plant height, number of leaves, leaf circumference, and wet biomass of harvested plants. The application of red onion and shallot extracts was carried out on green spinach plants aged seven days after planting (DAP) with a time interval of 1 week until 28 DAP. Observation of green spinach plant growth parameters began at the age of 14-35 DAP. Statistical analysis of the data using analysis of variance (ANOVA) and then the Duncan Multiple Range Test (DMRT) further t-test a 5% significance level. The results showed that red onion and shallot extracts affected all observed growth parameters of green spinach plants. Shallot extract with a concentration of 45% gave the best results on all green spinach plant growth parameters.